Al2O3-Cr2O3-ZnO / OH--H beta metal solid acid catalyst as well as preparation method and application thereof

By loading Al2O3, Cr2O3 and ZnO on the Hβ molecular sieve, Al2O3-Cr2O3-ZnO/OH--Hβ metal solid acid catalyst is formed, which solves the problems of many by-products, low conversion rate and short service life in the production process of ethyl acetate in the prior art, and achieves high efficiency, high selectivity and long service life.

CN119633893AActive Publication Date: 2025-03-18NANJING NORMAL UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411849390.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The prior art has problems such as many by-products, low raw material conversion rate, short service life, and difficult separation of catalysts and products when producing ethyl acetate. Although Hβ molecular sieve catalysts have high conversion rates, they are still inferior to industrial production standards.

Method used

A metal solid acid catalyst of Al2O3-Cr2O3-ZnO/OH--Hβ was developed, and the OH--Hβ molecular sieve was obtained by alkali treatment of Hβ molecular sieve, and Al2O3, Cr2O3 and ZnO were supported thereon to form a micromesoporous structure to improve catalytic activity.

Benefits of technology

The catalyst has been improved with high stability, anti-coking performance, conversion rate, selectivity and service life. The acetic acid conversion rate has reached 98.43%, the ethyl acetate selectivity has reached 100%, the mass content and yield have been significantly improved, and the service life has reached more than 1,200 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633893A_ABST
    Figure CN119633893A_ABST
Patent Text Reader

Abstract

The invention discloses an Al2O3-Cr2O3-ZnO / OH--H beta metal solid acid catalyst as well as a preparation method and application thereof, the catalyst comprises an OH--H beta molecular sieve carrier obtained by alkali treatment of an H beta molecular sieve, and Al2O3, Cr2O3 and ZnO are loaded on the OH--H beta molecular sieve carrier; wherein Al2O3 accounts for 1-10 wt% of the mass of the catalyst carrier, and Cr2O3 and ZnO respectively account for 1-15 wt% of the mass of the catalyst carrier. The preparation method comprises the following steps: carrying out roasting treatment, alkali treatment and ion exchange on an H [beta] molecular sieve to prepare an OH <->-H [beta] molecular sieve carrier with hierarchical pores, placing the carrier in a mixed aqueous solution composed of an aluminum salt, a chromium salt and a zinc salt with the same volume for equivalent-volume impregnation, and carrying out standing, drying and roasting to prepare the catalyst. The catalyst not only retains the characteristic of high stability of traditional micropores, but also has relatively high anti-coking performance, and has the advantages of high conversion rate, high selectivity, high yield and long service life for synthesis of ethyl acetate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid acid catalyst and a preparation method and application thereof, in particular to an Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst and its preparation method and application. Background Art

[0002] Ethyl acetate is an important organic fine chemical product, which is currently widely used in industrial production fields such as dyes, cosmetics, coatings, adhesives, plasticizers, artificial fibers, and medicines. With the restriction of the use of some toxic solvents at home and abroad, the market demand for ethyl acetate has increased significantly in recent years.

[0003] The methods for producing ethyl acetate reported in domestic and foreign literature mainly include: direct esterification, acetaldehyde condensation, ethanol dehydrogenation, and acetic acid / ethylene addition. There are two main ways to produce ethyl acetate industrially: liquid phase method and gas phase method. The liquid phase method mostly uses inorganic acid as a catalyst, which cannot be produced continuously, has many by-products and high energy consumption. The gas phase method mainly uses solid acid as a catalyst, which can react under normal pressure and produce continuously. Solid acid catalysts generally include inorganic salts, molecular sieves, composite oxides, etc.

[0004] At present, the process of producing ethyl acetate has many by-products, low raw material conversion rate, short service life, and difficulty in separating catalysts from products. Among them, Hβ molecular sieve has a higher conversion rate as a catalyst, which can improve the selectivity of the reaction and reduce energy consumption, but it is still far from the standard of industrial production. Therefore, the development of catalysts with high conversion rate, strong anti-coking ability and long service life has potential industrial application value. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide an Al2O3-Cr2O3-ZnO / OH having not only high stability and anti-coking performance, but also high conversion rate, selectivity and service life and a micro-mesoporous structure. - -Hβ metal solid acid catalyst;

[0006] The second object of the present invention is to provide the above-mentioned Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst preparation method;

[0007] The third object of the present invention is to provide the above-mentioned Al2O3-Cr2O3-ZnO / OH - -Application of Hβ metal solid acid catalyst in esterification reaction.

[0008] Technical solution: Al2O3-Cr2O3-ZnO / OH --Hβ metal solid acid catalyst, including OH obtained by treating Hβ molecular sieve with alkali - -Hβ molecular sieve support, the OH - -Hβ molecular sieve carrier is loaded with Al2O3, Cr2O3 and ZnO; wherein Al2O3 accounts for 1-10wt% of the catalyst carrier mass, Cr2O3 and ZnO account for 1-15wt% of the catalyst carrier mass respectively.

[0009] If the amount of loaded metal is too large, it will block the internal pores of the catalyst and reduce the specific surface area in contact with the reactants. If the amount of loaded metal is too small, the bimetallic synergy will be reduced and the reaction effect will be affected.

[0010] The above Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst preparation method, comprising the following steps:

[0011] (1) Hβ molecular sieve is calcined, treated with alkali and ion exchanged to obtain OH with multi-level pores - -Hβ molecular sieve carrier;

[0012] (2) Dissolve aluminum salt, chromium salt and zinc salt separately and mix them in equal volumes to form a mixed solution; - -Hβ molecular sieve carrier was impregnated in the mixed solution, and then calcined to obtain Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst.

[0013] Wherein, in step (1), the "multi-level pores" refer to OH - The -Hβ molecular sieve carrier includes pores of different sizes, including micropores and mesopores.

[0014] Wherein, in step (1), the calcination temperature is 400-500° C. and the calcination time is 4-6 hours.

[0015] Wherein, in step (1), the specific process of the alkali treatment is: according to the solid-liquid ratio (g / ml) of 1:10-20, the calcined and ground Hβ molecular sieve powder is fully mixed with the alkali solution with a concentration of 0.1-0.5 mol / L, stirred, impregnated and refluxed, treated at 60-70°C for 0.8-1.2h, cooled to room temperature, washed and filtered until the filtrate is neutral, the obtained filter cake is placed in a 100-120°C oven and dried for 6-10h, and the dried solid is ground into powder.

[0016] Wherein, in step (1), the specific process of ion exchange is: according to the solid-liquid ratio (g / ml) of 1:10 to 30, the powder obtained by alkali treatment is fully mixed with an NH4Cl solution with a concentration of 0.4 to 0.6 mol / L, the ion exchange is carried out at 60 to 80°C for 1 to 2 hours and filtered, and the mixture is repeated 2 to 4 times and then washed and filtered until no chloride ions are contained therein, and the obtained filter cake is placed in an oven at 100 to 120°C and dried for 6 to 10 hours, and then ground into powder after drying; and calcined to obtain an Hβ molecular sieve with a micro-mesoporous structure.

[0017] Wherein, in step (2), in the mixed solution, the concentrations of aluminum salt, chromium salt and zinc salt are 0.05-0.1 mol / L, 0.06-0.1 mol / L and 0.08-0.1 mol / L respectively. Preferably, the aluminum salt, chromium salt and zinc salt are dissolved in water to form an aqueous solution respectively; and equal volumes are mixed to form a mixed aqueous solution. The aluminum salt is selected from at least one of aluminum sulfate, aluminum chloride and aluminum nitrate nonahydrate; the chromium salt is selected from at least one of chromium chloride, chromium sulfite and chromium nitrate nonahydrate; the zinc salt is selected from at least one of zinc chloride, zinc sulfate and zinc nitrate hexahydrate.

[0018] Wherein, in step (2), the OH - The solid-liquid ratio of the Hβ molecular sieve carrier and the mixed solution is 1:1-5.

[0019] Wherein, in step (2), the immersion time is 12 to 24 hours.

[0020] Wherein, in step (2), drying is first performed after completion and then calcination is performed; the drying temperature is 100-110° C. and the drying time is 6-10 hours; the calcination temperature is 500-700° C. and the calcination time is 4-6 hours.

[0021] The above Al2O3-Cr2O3-ZnO / OH - -Application of Hβ metal solid acid catalyst in esterification reaction.

[0022] Among them, the above-mentioned Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst is used as a catalyst, and a mixed solution of ethanol and acetic acid is used as a reaction raw material to carry out an esterification reaction to prepare ethyl acetate.

[0023] The conditions of the esterification reaction are: 0.1-0.3 MPa, reaction temperature 100-140°C; mass space velocity of the reaction raw materials 0.3-0.9 h -1 .

[0024] Wherein, the mass ratio of the ethanol to the acetic acid is 1 to 2:1.

[0025] The reaction device used is a continuous tubular reactor.

[0026] Invention principle: Using alkali to modify Hβ will lead to the dissolution and removal of internal skeleton silicon, forming skeleton cavities and micro-mesoporous structures. Compared with the original molecular sieve, it has a larger specific surface area and greatly increases the active sites of the catalyst. In terms of the selection of loaded metals: Due to the Cr 3+ The ionic radius is Zn 2+ The ionic radius Small, Cr 3+ It can enter the ZnO lattice to form a solid solution Cr with a unit cell volume smaller than that of ZnO. x Zn 1-x O. Al 3+ The ionic radius is The ion radius is smaller than that of the other two metals, so it will greatly promote the solid solution Cr x Zn 1-x Formation of O. Solid solution Cr x Zn 1-x O will fill the framework holes in the NaOH / Hβ support, and the reduction of the unit cell volume will lead to the appearance of structural defects, which is conducive to the migration of oxygen anions in the solid solution and then generate oxygen vacancies, thus making the catalyst have the ability to release / store oxygen.

[0027] In the catalytic synthesis of ethyl acetate, in order to make up for the oxygen vacancies, -OH in the raw material CH3COOH will chemically adsorb on the oxygen vacancies, thereby promoting the release of -COCH3. The generated -COCH3 will replace the H on the -OH in the raw material ethanol, thereby generating ethyl acetate. The H replaced on the -OH will combine with the -OH adsorbed on the oxygen vacancy to generate H2O, and detach from the oxygen vacancy, so that the oxygen vacancy is generated again, thereby continuing to promote the release of -COCH3. The doping of Al2O3 in the catalyst of the present invention can greatly improve the dispersion of active species and the surface ion concentration of active species Cr2O3 and ZnO, the solid solution Cr x Zn 1-x O concentration, thereby increasing the number of L acids on the catalyst surface. Higher L acid sites help to add a proton to the carbonyl oxygen on the acid to form an oxonium ion, which has strong electrophilicity. Alcohol acts as a nucleophilic reagent to attack the carbonyl group to obtain a tetrahedral intermediate containing two hydroxyl groups. Through proton transfer, a molecule of water is eliminated to generate an ester, thereby promoting the reaction. Therefore, the catalyst of the present invention has a Lewis-oxygen vacancy synergistic catalytic effect.

[0028] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0029] (1) Al2O3-Cr2O3-ZnO / OH of the present invention- -Hβ catalyst not only has high stability and anti-coking performance, but also has high conversion rate, selectivity and service life; the catalyst of the present invention can simultaneously make the acetic acid conversion rate reach 98.43%, the ethyl acetate selectivity reach 100%, the mass content reach 57.05%, the yield reach 98.43%, and the service life reach more than 1200h. (2) In the preparation process of the catalyst of the present invention, equal volumes of aluminum salt, chromium salt and zinc salt are mixed to form a mixed aqueous solution, and then the molecular sieve carrier is immersed in the mixed aqueous solution. The loading amount of the three metals in the catalyst can be controlled by controlling the concentration of each of the three metal salts. Compared with the traditional dry method and the ordinary wet method, this method of preparing the loaded catalyst by impregnation is easier to control the loading amount, and the loading is more uniform, and the prepared catalytic activity is relatively high; (3) The preparation method of the catalyst of the present invention is simple and easy to operate; (4) The synthesis of ethyl acetate of the present invention uses a heterogeneous tubular reactor as a reaction device, realizes the continuous reaction process, and is easy to apply in industrial production; (5) The Al2O3-Cr2O3-ZnO / OH prepared by the present invention - -Hβ catalyst can be recycled and regenerated, and the regenerated catalyst still retains high catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD comparison diagrams of catalysts Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;

[0031] Figure 2 Figure 2 shows the N2 adsorption-desorption of the catalysts Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ obtained in Comparative Examples 1 and 2 and Example 1 of the present invention;

[0032] Figure 3 The pore size distribution diagrams of the catalysts Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;

[0033] Figure 4 NH3 adsorption-desorption diagram of catalysts Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;

[0034] Figure 5 SEM images of catalysts Hβ (a), NaOH-Hβ (b) and Al2O3-Cr2O3-ZnO / NaOH-Hβ (c) prepared in Comparative Examples 1 and 2 and Example 1 of the present invention;

[0035] Figure 6This is a trend chart of the experimental results of the life investigation of the catalyst Al2O3-Cr2O3-ZnO / NaOH-Hβ;

[0036] Figure 7 The effect of reaction temperature on acetic acid conversion and ethyl acetate mass content in Example 3 of the present invention;

[0037] Figure 8 Effect of mass space velocity on acetic acid conversion and ethyl acetate mass content and yield in Example 4 of the present invention;

[0038] Fig. 9 Effect of the raw material mass ratio on acetic acid conversion and ethyl acetate mass content in Example 5 of the present invention;

[0039] Fig.10 Effect of reaction pressure on acetic acid conversion and ethyl acetate mass content in Example 6 of the present invention. DETAILED DESCRIPTION

[0040] The present invention is described in further detail below.

[0041] Example 1

[0042] A method for preparing an Al2O3-Cr2O3-ZnO / NaOH-Hβ metal solid acid catalyst comprises the following steps:

[0043] (1) taking Hβ molecular sieve raw powder and calcining it at 500°C for 5h; mixing the calcined Hβ molecular sieve with 0.5mol / L alkaline solution, filtering it to neutrality, drying it at 110°C for 10h, and grinding the obtained solid into powder; using NH4Cl solution for ion exchange, repeating the above operation three times, washing with deionized water until the filtrate does not contain chloride ions, drying, grinding and calcining to obtain a micro-mesoporous Hβ molecular sieve, which is recorded as a multi-level pore NaOH-Hβ molecular sieve;

[0044] (2) 0.067 mol / L aluminum nitrate nonahydrate aqueous solution, 0.062 mol / L chromium nitrate nonahydrate aqueous solution and 0.084 mol / L zinc nitrate hexahydrate aqueous solution were mixed in equal volumes at a solution volume ratio of 1:1:1 to obtain a mixed aqueous solution; a NaOH-Hβ molecular sieve carrier was immersed in the mixed aqueous solution for 15 hours, wherein the solid-liquid ratio (g / ml) of the NaOH-Hβ molecular sieve carrier to the mixed aqueous solution was 1:2; then the fully immersed mixed solution was placed in an oven at 110° C. and dried for 10 hours to obtain a solid, which was ground into powder and placed in a muffle furnace for calcination at 500° C. for 5 hours to obtain a metal solid acid catalyst Al2O3-Cr2O3-ZnO / NaOH-Hβ; wherein Al2O3, Cr2O3 and ZnO each accounted for 5wt% of the mass of the catalyst carrier; the volumes of the aluminum nitrate nonahydrate aqueous solution, the chromium nitrate nonahydrate aqueous solution and the zinc nitrate hexahydrate aqueous solution were determined according to the mass of the NaOH-Hβ molecular sieve carrier.

[0045] The Al2O3-Cr2O3-ZnO / NaOH-Hβ prepared above was used as a catalyst to synthesize ethyl acetate. The specific operation steps are as follows:

[0046] First, 4 g of catalyst was added to the continuous tubular reaction tube, and a mixture of ethanol and acetic acid in a mass ratio of 1.53:1 was used as the reaction raw material for esterification reaction. The reaction conditions were: normal pressure, preheating temperature of 125 °C, reaction temperature of 120 °C, mass space velocity of 0.5 h -1 The raw materials were cooled after the reaction, and the esterification products were collected and detected by GC-7890Plus gas chromatography.

[0047] The relevant characterizations of the Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ catalysts in Example 1 are as follows: Figures 1 to 5 shown.

[0048] Figure 1 The XRD characterization diagrams of Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ catalysts are shown in Figure 2. Figure 1It can be seen that the three samples all have characteristic diffraction peaks of Hβ at 2θ of 7.8° and 22.4°, indicating that the process of alkali modification and loading of metal cases Al, Cr, and Zn has no effect on the crystal structure of Hβ. Among them, the diffraction peaks of NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ are significantly lower than those of Hβ, because the alkali solution has a desiliconization modification effect on the Hβ molecular sieve, which easily produces an amorphous molecular sieve skeleton structure, resulting in a decrease in the crystallinity of the sample; after the trimetallic composite modification, some molecular sieve channels are blocked or dissolved and destroyed, resulting in a further decrease in the crystallinity of the sample relative to the molecular sieve treated with alkali. At the same time, no obvious diffraction peaks of Al, Cr, and Zn were found in the spectrum, indicating that the content of the loaded metal is low, resulting in no corresponding signals being detected during the XRD measurement, or because the Al, Cr, and Zn loaded on NaOH-Hβ are evenly distributed on the catalyst surface and no obvious metal clusters are formed.

[0049] Figure 2 and Figure 3 The N2 adsorption-desorption curves and pore size distribution curves of three catalysts Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ are shown. Figure 2 It can be seen that in the low-pressure zone, the adsorption curve of Hβ rises rapidly, and adsorption occurs in the micropores, showing a typical type I isotherm, which proves the microporous structure of the Hβ sample. At the same time, in the high-pressure zone where P / P0>0.6, a typical H4-type hysteresis loop belonging to narrow slit pores can be observed, which indicates that there are irregular pore gaps between Hβ particles. The mesopore pore size distribution curve of the Hβ sample corresponds to the result of the isotherm. The mesopore pore size distribution diagram of the Hβ sample has a broad peak between 2 and 10 nm. The isotherms of Hβ and NaOH-Hβ samples are typical type I isotherms in the low-pressure zone, proving the existence of microporous structure in the sample. In the high-pressure zone, they are typical type IV isotherms with a large hysteresis loop, indicating that intramolecular mesoporous structures appear during the desiliconization process, forming a microporous-mesoporous hierarchical pore structure. By Figure 3 The pore size distribution diagram also shows that NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ samples have more mesopores than Hβ molecular sieve, and the mesopore size range is concentrated between 2 and 10 nm. However, the loading of Al2O3, Cr2O3 and ZnO may have a certain influence on the pore size and pore volume of the samples, resulting in the pore size and pore volume being slightly smaller than those of the NaOH-Hβ sample.

[0050] Figure 4The following is a graph showing the NH3 adsorption-desorption of three catalysts: Hβ, NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ. As can be seen from the figure, two NH3 desorption peaks appeared in the two samples within the range of 100℃~600℃, located between 50~250℃ and 250~425℃, respectively, representing the weak acid center and medium-strong acid center of the samples, and the weak acid content was greater than the medium-strong acid content; after alkali treatment, the acid content of NaOH-Hβ and Al2O3-Cr2O3-ZnO / NaOH-Hβ was higher than that of the original Hβ powder, because the acidity of the Hβ molecular sieve mostly comes from the framework aluminum. While dissolving silicon, the silicon vacancies are occupied by aluminum, and bridge hydroxyl groups are formed, thereby increasing the acid content to a certain extent. Among them, the total acid content of Al2O3-Cr2O3-ZnO / NaOH-Hβ is greater than that of NaOH-Hβ. This is because the doping of Al2O3, Cr2O3 and ZnO fills the silicon vacancies of NaOH-Hβ molecular sieve, and there are mainly Lewis acid centers on the surfaces of Al2O3, Cr2O3 and ZnO. The synergistic effect between the three oxides increases the catalytic activity of the catalyst to a certain extent.

[0051] Figure 5 (a) is the SEM image of Hβ catalyst. Figure 5 (b) is the SEM image of NaOH-Hβ catalyst. Figure 5 (c) is the SEM image of Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst. Figure 5 It can be seen that before the alkali treatment, the surface of the Hβ molecular sieve is relatively neat and flat, and the crystal morphology is mostly cubic; after the alkali treatment, the molecular sieve has changed, and many channels have appeared on the crystal surface, becoming rough and uneven, and the edges and corners have disappeared; this is mainly attributed to the alkaline solution dissolving the silicon species in the molecular sieve, generating holes in the molecular sieve skeleton, and thus forming a micro-mesoporous structure. In addition, it can be seen that the molecular sieve particles after alkali treatment are more uniform in size, which is conducive to the esterification reaction.

[0052] The life test of the prepared Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst was carried out, and the results are as follows Figure 6 As shown. Figure 6 It can be seen that throughout the experiment, as time goes by, the activity and selectivity of the Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst are relatively stable, which means that the catalyst has a high catalytic activity and a long catalyst life of 1200 h.

[0053] Example 2

[0054] The basic steps are the same as those in Example 1, except that the loading amounts of Cr2O3 and ZnO in the catalyst are different, as shown in Table 1.

[0055] This example investigates the effect of Cr2O3 and ZnO loading on the catalytic performance of the metal solid acid catalyst Al2O3-Cr2O3-ZnO / NaOH-Hβ. The effects of different Cr2O3 and ZnO loadings on the conversion rate of acetic acid and the yield of ethyl acetate are shown in Table 1.

[0056] Table 1 Effect of different metal loadings on acetic acid conversion and ethyl acetate mass content and yield

[0057]

[0058]

[0059] It can be seen from Table 1 that when the Al2O3 content is 5wt%, the Cr2O3 content is 5wt%, and the ZnO content is 5wt%, using Al2O3-Cr2O3-ZnO / NaOH-Hβ as the catalyst can make the acetic acid conversion rate reach 98.43%, the mass content of ethyl acetate reach 57.05%, the selectivity reach 100%, and the yield reach 98.43%.

[0060] Example 3

[0061] The basic steps are the same as those in Example 1, except that the reaction temperature during the synthesis of ethyl acetate is different. The reaction temperatures are 100°C, 110°C, 120°C, 130°C, and 140°C, respectively. The experimental results are shown in FIG. Figure 7 shown.

[0062] This example is a single-dimensional experiment of the reaction temperature in the synthesis of ethyl acetate. Figure 7 It can be seen that different reaction temperatures have a great influence on the catalytic activity of the Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst. As the reaction temperature increases, the conversion rate of acetic acid and the mass content of ethyl acetate show a trend of first increasing and then stabilizing. This is because the temperature is too low, the reaction raw materials are not completely gasified, the contact is not comprehensive, the reaction is not complete, which is not conducive to the normal progress of the reaction, resulting in a low conversion rate of acetic acid; when the temperature is too high, the reaction system is completely gasified, the reaction tends to be complete, and the conversion rate of acetic acid tends to be stable. Therefore, considering all factors, the most suitable reaction temperature for this reaction is 120℃.

[0063] Example 4

[0064] The basic steps are the same as those in Example 1, except that the mass space velocity during the synthesis of ethyl acetate is different. The mass space velocity is 0.3h -1 , 0.5h -1 、0.7h -1 , 0.9h -1 , 1.1h -1 ,

[0065] This example is a single-dimensional experiment on mass space velocity in the synthesis of ethyl acetate. Figure 8 As shown. Figure 8 It can be seen that different mass space velocities affect the catalytic activity of the Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst. As the mass space velocity increases, the reaction residence time decreases, resulting in a gradual decrease in the conversion rate of acetic acid and the mass content of ethyl acetate; as the mass space velocity decreases, the reaction residence time increases, and the conversion rate of acetic acid and the mass content of ethyl acetate gradually increase and tend to be flat. Therefore, considering all factors, the most suitable mass space velocity for this reaction is 0.5h -1 .

[0066] Example 5

[0067] The basic steps are the same as those in Example 1, except that the raw material ratios in the synthesis of ethyl acetate are different. The mass ratios of ethanol and acetic acid in the raw materials are 1.23:1, 1.38:1, 1.53:1, 1.69:1, and 1.84:1, respectively.

[0068] This example is a single-dimensional experiment of the raw material ratio in the synthesis of ethyl acetate. The results are as follows Fig. 9 As shown. Fig. 9 It can be seen that different raw material ratios have a great influence on the catalytic activity of Al2O3-Cr2O3-ZnO / NaOH-Hβ catalyst. With the increase of ethanol mass content in the raw material, the conversion rate of acetic acid gradually increases. When the mass ratio of ethanol to acetic acid is greater than 1.53, the yield of ethyl acetate remains basically stable, but the higher ethanol content in the reaction product will increase the cost of subsequent product separation. Comprehensive consideration, the most suitable raw material mass ratio for this reaction is m(ethanol):m(acetic acid)=1.53:1.

[0069] Example 6

[0070] The basic steps are the same as those in Example 1, except that the reaction pressures during the synthesis of ethyl acetate are different. The reaction pressures are 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, and 0.3 MPa, respectively. The results are shown in FIG. Fig.10 As shown. Fig.10 It can be seen that different pressures have little effect on the activity of the catalyst. In the pressure range of 0.1-0.15MPa, the acetic acid conversion rate and ethyl acetate yield fluctuate slightly. When the pressure is greater than 0.15MPa, the acetic acid conversion rate and ethyl acetate yield drop rapidly. This is because the boiling point of acetic acid increases due to the increase in pressure, and it fails to vaporize at 120°C, resulting in a decrease in the contact area of ​​the reactants and a significant decrease in the reaction conversion rate. Therefore, considering comprehensively, the more suitable pressure for this reaction is 0.1MPa.

[0071] Example 7

[0072] The basic steps are the same as those in Example 1. Based on the single-dimensional investigation, L9(3 4 )The orthogonal experiment is shown in Table 2 below.

[0073] Table 2L9(3 4 ) Orthogonal experimental conditions and results

[0074]

[0075] Table 2 shows that pressure has the greatest impact on acetic acid conversion, and mass space velocity has the least impact on reaction rate. The orthogonal optimization results combined with actual industrial production conditions show that the optimal combination is a reaction temperature of 120°C and a mass space velocity of 0.5h -1 , raw material mass ratio is 1.53:1, and the reaction pressure is 0.1MPa.

[0076] Comparative Example 1

[0077] On the basis of Example 1, the difference from Example 1 is that the Hβ molecular sieve raw powder in Example 1 is used as a catalyst to synthesize ethyl acetate.

[0078] Comparative Example 2

[0079] On the basis of Example 1, the difference from Example 1 is that the NaOH-Hβ molecular sieve prepared in Example 1 is used as a catalyst to synthesize ethyl acetate.

[0080] The esterification performance of Hβ molecular sieve raw powder, NaOH-Hβ molecular sieve, and Al2O3-Cr2O3-ZnO / NaOH-Hβ was compared. Compared with Hβ molecular sieve raw powder and NaOH-Hβ molecular sieve, the catalytic activity of Al2O3-Cr2O3-ZnO / NaOH-Hβ was significantly improved, the conversion rate of acetic acid was increased to 98.43%, and the selectivity of ethyl acetate was increased to 100%.

[0081] Comparative Example 3

[0082] Based on Example 1, the difference from Example 1 is that the solid-liquid ratio of the NaOH-Hβ molecular sieve carrier to the metal salt mixed liquid is different. The effects of the catalytic activity of the catalysts prepared with different solid-liquid ratios are shown in Table 3.

[0083] Table 3 Effect of different solid-liquid ratios on acetic acid conversion and ethyl acetate mass content and yield

[0084] Solid-liquid ratio (g / ml) Acetic acid conversion rate / % Ethyl acetate mass content / % Ethyl acetate yield / % 1:1 95.89 55.57 95.89 1:2 98.43 57.04 98.43 1:3 96.15 55.72 96.15 1:4 93.89 54.41 93.89 1:5 90.26 52.31 90.26

[0085] It can be seen from Table 3 that as the solid-liquid ratio gradually increases, the acetic acid conversion first increases and then decreases, that is, the catalytic performance of the catalyst first increases and then decreases, reaching the highest catalytic performance when the solid-liquid ratio is 1: 2. The reason for this phenomenon is that if the solid-liquid ratio is too low, the metal salt load will stack and block the pores, and if the solid-liquid ratio is too high, the metal salt and carrier load will not be sufficient, reducing the catalytic performance.

[0086] Comparative Example 4

[0087] On the basis of Example 1, the difference from Example 1 is that the volume impregnation ratio of the metal salt solution is different. The volume of the aluminum salt solution is kept unchanged, and the volume ratio of the chromium salt and zinc salt solutions is changed. The effects of different volume impregnation ratios on the catalytic performance of the catalyst are shown in Table 4.

[0088] Table 4 Effect of different volume ratios of catalysts on acetic acid conversion and ethyl acetate mass content and yield

[0089]

[0090] It can be seen from Table 4 that the catalyst obtained by equal volume impregnation has the best catalytic effect.

[0091] Comparative Example 5

[0092] Based on Example 1, the difference from Example 1 is that the calcination temperature after the metal salt is loaded is different. The influence of different calcination temperatures on the catalytic performance of the catalyst is shown in Table 5.

[0093] Table 5 Effect of catalysts at different calcination temperatures on acetic acid conversion and ethyl acetate mass content and yield

[0094] Calcination temperature (℃) Acetic acid conversion rate / % Ethyl acetate mass content / % Ethyl acetate yield / % 400 94.66 54.86 94.66 450 97.35 56.42 97.35 500 98.43 57.04 98.43 550 98.44 57.05 98.44 600 98.43 57.04 98.43

[0095] It can be seen from Table 5 that with the increase of calcination temperature, the catalyst performance first increases and then tends to be stable. The reason is that when the temperature is too low, the metal salt loaded on the carrier cannot be completely converted into oxides. When the temperature reaches about 500°C, the loaded metal salt is completely converted into oxides. Continuing to increase the temperature does not change the total amount of oxides. At this time, the catalytic performance remains unchanged and reaches stability. Therefore, the calcination temperature is selected as 500°C.

[0096] Comparative Example 6

[0097] Based on Example 1, the difference from Example 1 is that the types of loaded metal oxides are different. The effects of loading of different types of metal oxides on the catalyst performance are shown in Table 6.

[0098] Table 6 Effect of catalysts of different element types on acetic acid conversion rate and ethyl acetate mass content and yield

[0099] Element Type Acetic acid conversion rate / % Ethyl acetate mass content / % Ethyl acetate yield / % Al, Zn, Cr 98.43 57.04 98.43 Al, Zn, Nb 96.43 55.89 96.43 Al, Zn, La 97.78 56.67 97.78 Zn, Cr, Nb 95.43 55.31 95.43 Zn, Cr, La 95.13 55.13 95.13 Cr, Nb, La 91.58 53.07 91.58

[0100] It can be seen from Table 6 that the catalyst loaded with Al, Zn, and Cr has the best catalytic effect. The reason is that Zn and Cr will form a solid solution and have a good catalytic effect on the forward esterification reaction. The doping of Al element will make Zn and Cr form a solid solution better and play a synergistic catalytic role. Therefore, a combination of Al, Zn, and Cr is selected to be loaded on the carrier.

Claims

1. Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst, characterized in that Including OH obtained by alkali treatment of Hβ molecular sieve - -Hβ molecular sieve support, the OH - -Hβ molecular sieve carrier is loaded with Al2O3, Cr2O3 and ZnO; Among them, Al2O3 accounts for 1-10wt% of the mass of the catalyst carrier, and Cr2O3 and ZnO account for 1-15wt% of the mass of the catalyst carrier respectively.

2. The Al2O3-Cr2O3-ZnO / OH according to claim 1 - -Hβ metal solid acid catalyst preparation method, characterized in that, The following steps are involved: (1) Hβ molecular sieve is calcined, treated with alkali and ion exchanged to obtain OH with multi-level pores - -Hβ molecular sieve carrier; (2) Dissolve aluminum salt, chromium salt and zinc salt separately and mix them in equal volumes to form a mixed solution; - -Hβ molecular sieve carrier was impregnated in the mixed solution, and then calcined to obtain Al2O3-Cr2O3-ZnO / OH - -Hβ metal solid acid catalyst.

3. Al2O3-Cr2O3-ZnO / OH according to claim 2 - -Hβ metal solid acid catalyst preparation method, characterized in that, In step (2), in the mixed solution, the concentrations of aluminum salt, chromium salt and zinc salt are 0.05-0.1 mol / L, 0.06-0.1 mol / L and 0.08-0.1 mol / L respectively.

4. Al2O3-Cr2O3-ZnO / OH according to claim 2 - -Hβ metal solid acid catalyst preparation method, characterized in that, In step (2), the OH - The solid-liquid ratio of the Hβ molecular sieve carrier and the mixed solution is 1:1-5.

5. Al2O3-Cr2O3-ZnO / OH according to claim 2 - -Hβ metal solid acid catalyst preparation method, characterized in that, In step (2), the immersion time is 12 to 24 hours.

6. Al2O3-Cr2O3-ZnO / OH according to claim 2 - -Hβ metal solid acid catalyst preparation method, characterized in that, In step (2), after completion, drying is first performed and then calcination is performed; the drying temperature is 100-110° C. and the drying time is 6-10 hours; the calcination temperature is 500-700° C. and the calcination time is 4-6 hours.

7. Al2O3-Cr2O3-ZnO / OH according to claim 2 - -Hβ metal solid acid catalyst preparation method, characterized in that, In step (1), the roasting temperature is 400-500°C and the time is 4-6 hours; the alkali treatment solution is a 0.1-0.5 mol / L alkali solution and the solid-liquid ratio is 1:10-20; the solution used for ion exchange is a 0.4-0.6 mol / L NH4Cl solution, the number of ion exchanges is 2-4 times, and the ion exchange time is 1-2 hours / time.

8. The Al2O3-Cr2O3-ZnO / OH according to claim 1 - -Application of Hβ metal solid acid catalyst in esterification reaction.

9. The use according to claim 8, characterized in that: The Al2O3-Cr2O3-ZnO / OH according to claim 1 - -Hβ metal solid acid catalyst is used as a catalyst, and a mixed solution of ethanol and acetic acid is used as a reaction raw material to carry out an esterification reaction to prepare ethyl acetate.

10. The application according to claim 9, characterized in that: The conditions of the esterification reaction are: 0.1-0.3 MPa, reaction temperature 100-140°C; mass space velocity of the reaction raw materials 0.3-0.9 h -1 .

Citation Information

Patent Citations

  • Preparation method of self-supporting metal-modified Beta molecular sieve and application thereof in synthesizing of isoprene

    CN107899608A

  • Method for synthesizing n-butyl acetate through ester exchange path

    CN108503547A

  • Preparation method and application of catalyst for preparing 2-methylnaphthalene / 2, 6-dimethylnaphthalene from synthesis gas and naphthalene through one-step method

    CN112657538A

  • Catalyst for catalyzing synthesis gas with high carbon hydrogen ratio to prepare methyl acetate as well as preparation method and application of catalyst

    CN114570419A

  • Synthesis method of N, N-dimethylaniline

    CN116003262A